A Governance-Structure Approach to Voluntary Organizations - Enjolras, Bernard (Nonprofit and voluntary sector quarterly, 2009)
This article develops a governance-structure theoretical understanding of voluntary organizations. Voluntary organizations are seen as governance structures reinforcing the norm of (generalized or balanced) reciprocity, making possible the pooling of resources based on the reciprocity principle. Voluntary organizations’ governance structure presents some specific features in terms of formal ends, ownership, residual claims, decision-making procedures, accountability, checks and balances, control procedures, and embedded incentives facilitating collective action oriented toward public or mutual interest or toward advocacy. Because the voluntary governance structure is also compatible with several types of coordination mechanisms, voluntary organizations are able to operate in complex environments, mobilizing resources from market operations, governmental subsidies, or from reciprocity (volunteering, donations) while pursuing civic and democratic objectives. Their governance structure allows them to mitigate coordination failures and remain comparatively more efficient than other organizational forms. However, voluntary organizations may be subject to governance failures, the result of which could undermine trustworthiness and efficiency.